1999
DOI: 10.1001/archneur.56.8.927
|View full text |Cite
|
Sign up to set email alerts
|

Association of Ipsilateral Motor Automatisms and Contralateral Dystonic Posturing

Abstract: The association of ipsilateral motor automatisms and contralateral dystonic posturing may help to differentiate MTLE from NTLE with a reliable lateralizing value. This clinical association may reflect a specific pattern in the spread of the ictal discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Ipsilateral motor automatisms associated with contralateral dystonic posturing during temporal lobe originating seizures have been well-described. 1,2 Sixteen (27%) of 60 patients with TLE had ipsilateral automatisms associated with contralateral dystonic posturing in one study. 1 Three of their patients, one with mesial TLE and two with neocortical TLE, had contralateral motor automatisms without dystonia.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Ipsilateral motor automatisms associated with contralateral dystonic posturing during temporal lobe originating seizures have been well-described. 1,2 Sixteen (27%) of 60 patients with TLE had ipsilateral automatisms associated with contralateral dystonic posturing in one study. 1 Three of their patients, one with mesial TLE and two with neocortical TLE, had contralateral motor automatisms without dystonia.…”
Section: Discussionmentioning
confidence: 97%
“…1,2 Sixteen (27%) of 60 patients with TLE had ipsilateral automatisms associated with contralateral dystonic posturing in one study. 1 Three of their patients, one with mesial TLE and two with neocortical TLE, had contralateral motor automatisms without dystonia. Motor automatisms were exclusively ipsilateral to the side of seizure origin in eight (30%) of 27 patients with TLE in another study which did not describe the origin of the seizures within the temporal lobe, neuroimaging findings, or pathology.…”
Section: Discussionmentioning
confidence: 97%
“…These differences are summarized in Table 1. Dupont et al [32] compared the ictal semiology of 45 mTLE patients with 13 nTLE patients and found that contralateral dystonic posturing with ipsilateral automatisms occurred in a third of the mTLE group but was never seen in those with nTLE. Auditory and vertiginous auras have been associated with the temporal neocortex, and visceral sensations and fear with the mesial temporal lobe [23, 33].…”
Section: Clinical Semiologymentioning
confidence: 99%
“…In some studies, features such as contralateral dystonic posture, ipsilateral manual automatisms, early onset non-forced ipsilateral head deviation, contralateral forced head deviation before secondary generalisation, ictal speech, ictal vomiting, postictal aphasia, partial responsiveness, postictal coughing and nose wiping have been demonstrated to be essential for lateralisation. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] However, in these studies, the pathological results were not homogeneous, 1,2,4-7,9-13,15-17 and patients were diagnosed with medial or lateral temporal lobe epilepsy, thus forming a heterogeneous group. 1,2,4,6,9,10,12,13,[15][16][17] In our study, a homogeneous group with hippocampal sclerosis was evaluated with regard to behavioural differences depending on the seizure source in the temporal lobe and on the patient's gender.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Considering the importance of ictal semiology before epilepsy surgery, many groups have analysed this aspect and reported that some features can have a lateralising effect. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] However, most of these studies did not describe the pathological details or the localisation of these lesions clearly. Further, other groups of patients did not have homogeneous pathological findings.…”
Section: Introductionmentioning
confidence: 99%